Biofilm over teeth and restorations: What do we need to know?. Issue 6 (June 2017) - Lin, Nancy J.
Graphical abstract: Highlights: Oral biofilms are heterogeneous microbial communities critical to health. Biofilm attributes include constituents (who), quantity, structure, and function. Measurement methods should be appropriate, and their limitations should be known. Efforts to improve reproducibility in biofilm experiments are underway. Normalizing results and using multiple methods reduces results ambiguity. Abstract: Objective: The goal of this manuscript is to provide an overview of biofilm attributes and measurement approaches in the context of studying biofilms on tooth and dental material surfaces to improve oral health. Methods: A historical perspective and terminology are presented, followed by a general description of the complexity of oral biofilms. Then, an approach to grouping measurable biofilm properties is presented and considered in relation to biofilm-material interactions and material design strategies to alter biofilms. Finally, the need for measurement assurance in biofilm and biofilm-materials research is discussed. Results: Biofilms are highly heterogeneous communities that are challenging to quantify. Their characteristics can be broadly categorized into constituents (identity), quantity, structure, and function. These attributes can be measured over time and in response to substrates and external stimuli. Selecting the biofilm attribute(s) of interest and appropriate measurement methods will depend on the application and, in the case of antimicrobial therapies, the strategic approach and expected mechanism of action. To provide measurement assurance, community accepted protocols and guidelines for minimum data and metadata should be established and broadly applied. Consensus standards may help to streamline testing and demonstration of product claims. Significance: Understanding oral biofilms and their interactions with tooth and dental material surfaces holds great promise for enabling improvements in oral and overall human health. Both substrate and biofilm properties should be considered to develop a more thorough understanding of the system.